Polypill use for the prevention of cardiovascular disease: A position paper - Araújo, Francisco (2023)
Cardiovascular (CV) guidelines stress the need for global intervention to manage risk factors and reduce the risk of major vascular events. Growing evidence supports the use of polypill as a strategy to prevent cerebral and cardiovascular disease, however it is still underused in clinical practice. This paper presents an expert consensus aimed to summarize the data regarding polypill use. The authors consider the benefits of polypill and the significant claims for clinical applicability. Potential advantages and disadvantages, data regarding several populations in primary and secondary prevention, and pharmacoeconomic data are also addressed.